2016
DOI: 10.1136/bmjopen-2015-009948
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement by suicide as a risk factor for suicide attempt: a cross-sectional national UK-wide study of 3432 young bereaved adults

Abstract: ObjectivesUS and UK suicide prevention strategies suggest that bereavement by the suicide of a relative or friend is a risk factor for suicide. However, evidence is lacking that the risk exceeds that of any sudden bereavement, is specific to suicide, or applies to peer suicide. We conducted the first controlled UK-wide study to test the hypothesis that young adults bereaved by suicide have an increased risk of suicidal ideation and suicide attempt compared with young adults bereaved by other sudden deaths.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
169
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(186 citation statements)
references
References 28 publications
9
169
0
2
Order By: Relevance
“…These and other shared familial and environmental risk factors for mental illness and suicidal behavior (35,36), together with the additional risk conferred by suicide bereavement (4,5), identifies this group of relatives as being at higher risk of suicidal behavior. Their helpseeking behavior is likely to have been conditioned by the stigma associated with their relative's mental illness (37) and further influenced by the stigma of suicide (6-9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other shared familial and environmental risk factors for mental illness and suicidal behavior (35,36), together with the additional risk conferred by suicide bereavement (4,5), identifies this group of relatives as being at higher risk of suicidal behavior. Their helpseeking behavior is likely to have been conditioned by the stigma associated with their relative's mental illness (37) and further influenced by the stigma of suicide (6-9).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of these patients, NHS guidelines recommend that clinical teams offer families and carers "prompt and open information" and "appropriate and effective support" and involve them in a routine postsuicide review (16). No previous studies have explored the extent to which relatives are offered such support, despite growing evidence describing the vulnerabilities of persons bereaved by suicide (4,5). Psychiatric services that involve family members in postsuicide multidisciplinary reviews have shown local reductions in suicide rates, suggesting systemic benefits (17).…”
mentioning
confidence: 99%
“…We analysed data from the UCL Bereavement Study [8,9]. This was a UK-wide cross-sectional survey of young adults aged 18–40 working and/or studying at UK higher education institutions (HEIs) who had experienced the sudden bereavement of a close friend or relative.…”
Section: Methodsmentioning
confidence: 99%
“…This study had focused on young adults due to concerns about their risk of suicide [18] and the difficulties of engaging young suicidal men with services [19]. Full details of sampling for this closed online survey have been described elsewhere, including the survey instrument (see Supplementary Materials) [8,9]. Sampling via institution-wide email lists (to all staff and students) avoided the biases associated with recruiting a help-seeking sample, and was felt to be the most efficient, comprehensive and pragmatic means of recruiting a hard-to-reach population of young adults [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation